Architectural factors for infection and disease control - Bliss, AnnaMarie; Kopec, Dak. ([S.l.] : Routledge, 2023)
This edited collection explores disease transmission and the ways that the designed environment has promoted or limited its spread. It discusses the many design factors that can be used for infection and disease control through lenses of history, public health, building technology, design, and education. This book calls on designers to consider the role of the built environment as the primary source of bacterial, viral, and fungal transfers through fomites, ventilation systems, and overcrowding and spatial organization. Through 19 original contributions, it provides an array of perspectives to understand how the designed environment may offer a reprieve from disease. The authors build a historical foundation of infection and disease, using examples ranging from lazarettos to leprosy centers to show how the ability to control infection and disease has long been a concern for humanity. The book goes on to discuss disease propagation, putting forth a variety of ideas to control the transmission of pathogens, including environmental design strategies, pedestrian dynamics, and open space. Its final chapters serve as a prospective way forward, focusing on COVID-19 and the built environment in a post-pandemic world. Written for students and academics of architecture, design, and urban planning, this book ignites creative action on the ways to design our built environment differently and more holistically. Please note that research on COVID-19 has exponentially grown since this volume was written in October 2020. References cited reflect the evolving nature of research studies at that time.
Keywords: ARCHITECTURE / General; ARCHITECTURE / Design & Drafting; ARCHITECTURE / Interior Design / General; Buildings -- Health aspects; Architecture -- Health aspects; Environmental health; Communicable diseases -- Transmission -- Prevention